International human rights and humanitarian law - Provost, René (Cambridge University, 2013)
Provost analyses systemic similarities and differences between the two to explore how they are each built to achieve their similar goal. He details the dynamics of human rights and humanitarian law, revealing that each performs a task for which it is better suited than the other, and that the fundamentals of each field remain partly incompatible. This helps us understand why their norms succeed in some ways and fail - at times spectacularly - in others. Provost's study represents innovative and in-depth research, covering all relevant materials from the UN, ICTY, ICTR, and regional organizations in Europe, Africa and Latin America. This will interest to academics and graduate students in international law and international relations, as well as legal practitioners in related fields and NGOs active in human rights.